Hipertensión intracraneal - Chimbo Chacha, Holger Fabricio;Myriam; Patricia Guamán Arias (2018)
The intracranial pressure (ICH) is the ratio between the skull and its content or brain compartment that is made up of the parenchyma, and the cranial blood volume (CSV) and the cerebrospinal fluid (CSF) also the cranial perfusion (CSP) is the difference between mean arterial pressure (MAP) and intracranial pressure (ICP). The intracranial hypertension (ICH) defines by that measurement inside the cranial base that is the result of the interaction in the continent of the skull, which contains the encephalon and the cerebrospinal fluid and blood, the pathology of intracranial hypertension leads to a high mortality both in men and women. Currently the technology and the improvement in invasive techniques to monitor the intracranial pressure of the patient, as well as the continuous updating of the interventions and the care and knowledge about its effects in this pathology, makes the nursing team of the Intensive care complies with effective, holistic and quality care for the patient's well-being. It is very important to know and treat in the shortest possible time this pathology, if to prevent secondary injuries that can affect the patient, the processes of nursing care in this pathology are crucial to keep the patient stable and to reduce hospital stay.